A Review of Preconcentrator Materials, Flow Regimes and Detection Technologies for Gas Adsorption and Sensing (Adv. Mater. Interfaces 20/2022). Issue 20 (12th July 2022) - Chowdhury, Aminur Rashid; Lee, Tse‐Ang; Day, Coco; Hutter, Tanya
Abstract : Gas Preconcentrators Gas preconcentrators are used to lower the detection limit of gas sensors. In article number 2200632, Aminur Chowdhury, Tanya Hutter, and co‐workers review the progress in gas preconcentrators focusing on porous materials. Detection technologies, integration, current limitations and improvement opportunities are also presented.